Literature Review: Immersive Technology as a Teaching Aid in the Health Sector - Mutyara, Dehana; Adisusilo, Anang Kukuh; Abdillah, Bima Ahmad Perkasa (IC-ITECHS, 2024)
The increasing complexity of healthcare education and the limitations of traditional teaching methods necessitate innovative approaches to meet global demands for skilled professionals. Immersive technologies, including Virtual Reality (VR), Augmented Reality (AR), Mixed Reality (MR), and Extended Reality (XR), offer transformative potential by providing interactive, lifelike simulations that bridge theoretical knowledge and practical skills. This study employs a systematic literature review alongside case studies and interviews with educators and students to assess the effectiveness of these technologies in healthcare training. Results reveal significant improvements in learner engagement, conceptual understanding, skill acquisition, and empathy, with particular benefits for inclusive and adaptive learning. However, barriers such as high costs, accessibility challenges, and ethical concerns persist, limiting widespread implementation. Practical recommendations are proposed to overcome these challenges through scalable, cost-effective solutions and interdisciplinary collaboration. This research highlights the global potential of immersive technologies to revolutionize healthcare education, fostering equity, inclusivity, and the development of a competent and empathetic healthcare workforce.